Cortical hypometabolism as a predictor of intermittent theta burst stimulation response in treatment-resistant depression patients: An open-label study - Nidhisha Bajaj; Nand Kumar; Rakesh Kumar; Vaibhav Patil; Anshul Sharma (Indian Journal of Psychiatry)
Background: Intermittent theta burst stimulation (iTBS) is an accepted and approved brain stimulation technique to treat patients with treatment-resistant depression. Aim: Using neuroimaging, this open-label study aimed to predict the response by observing glucose metabolism with the help of 18-FDG PET scan. Methods: A total of 25 treatment-resistant depression patients received 15 sessions of iTBS on the left dorsolateral prefrontal cortex. Two FDG-PET scans were done for all the patients. Fifty-six percent of patients responded to treatment with iTBS. Results: We found that there was hypometabolism in left and right prefrontal lateral regions, left and right inferior parietal regions, and left prefrontal medial regions at baseline but no statistically significant difference in the metabolism between responders and nonresponders. Conclusion: We did not find any statistically significant difference in the metabolism between responders and nonresponders in any brain regions at T0 as well as T1. Further large-scale studies are required.